Effect of Potassium Fertilizer Dose and Frequency of PSB Application on the Productivity of Melon - Rahmawati, Irene; Sulistyono, Agus; Santoso, Juli (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
nThis1studyiaimsoto increase melon fruit yield by determiningpthe effectoof theoright doseoof potassium fertilizer,nthe effect ofithe frequency of Photosynthetic Bacteria (PSB) administration and thepeffect ofpthepinteraction betweenpthe doseiof potassiumifertilizer and the frequency of PSB administration on melon fruit productivity. The studyiused a FactorialrRandomizedrBlock Designr(RAK) withrtwo main factors.pThe firstpfactor isithe doseiof potassium fertilizero(K0: without, K:9g/plant, K2:10g/plant, K3:11g/plant).pThe second factoriis theffrequency ofiPSB administration (F0: without, F1:1x a week, F2:2x a week, F3:3x a week). Each factor consists of 4 levels. The parameters observed include fruit weight per plant, fruitidiameter, fruittflesh thicknessaandisweetness level.iData will be analyzed using ANOVA. Theiresults oftthe studyiconcluded thatithe single factoriof potassium fertilizer and PSB doses significantly affected the fruit diameter and fruit flesh thickness. The interaction of potassium fertilizer and PSB administration significantly affected the fruitpweight per-plant andithe level of-sweetness. Thisistudy provides information for melon farmers to manage fertilization and PSB applications efficiently, so as to increase productivity.